ELECTIONS IN INDIAN DEMOCRACY -MEDIA OVERVIEW - Dudankar, Nagaveni; K, Mahalinga (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Elections are the cornerstone of Indian democracy, reflecting the will of the people in shaping governance. Media, as the fourth pillar of democracy, plays a crucial role in informing, educating, and engaging the electorate during elections. From traditional platforms like print and broadcast media to the transformative influence of digital and social media, the role of media in elections has evolved significantly. It serves as a powerful tool for disseminating information, shaping public opinion, and fostering electoral participation. However, challenges such as media bias, paid news, fake information, and the influence of political funding threaten its integrity. Regulatory frameworks by bodies like the Election Commission of India (ECI) and the Press Council of India aim to uphold fairness and transparency in electoral coverage. This paper explores the dynamic relationship between media and elections in India, highlighting its impact on democracy, challenges faced, and the path forward for responsible media practices.